Hsp90-binding immunophilins link p53 to dynein during p53 transport to the nucleus - Galigniana, M.D. (2004)
The tumor suppressor protein p53 is known to be transported to the nucleus along microtubular tracks by cytoplasmic dynein. However, the connection between p53 and the dynein motor protein complex has not been established. Here, we show that hsp90·binding immunophilins link p53·hsp90 complexes to dynein and that prevention of that linkage in vivo inhibits the nuclear movement of p53. First, we show that p53·hsp90 heterocomplexes from DLD-1 human colon cancer cells contain an immunophilin (FKBP52, CyP-40, or PP5) as well as dynein. p53·hsp90·immunophilin·dynein complexes can be formed by incubating immunopurified p53 with rabbit reticulocyte lysate, and we show by peptide competition that the immunophilins link via their tetratricopeptide repeat domains to p53-bound hsp90 and by means of their PPIase domains to the dynein complex. The linkage of immunophilins to the dynein motor is indirect by means of the dynamitin component of the dynein-associated dynactin complex, and we show that purified FKBP52 binds directly by means of its PPIase domain to purified dynamitin. By using a temperature-sensitive mutant of p53 where cytoplasmic-nuclear movement occurs by shift to permissive temperature, we show that p53 movement is impeded when p53 binding to hsp90 is inhibited by the hsp90 inhibitor radicicol. Also, nuclear movement of p53 is inhibited when immunophilin binding to dynein is competed for by expression of a PPIase domain fragment in the same manner as when dynein linkage to cargo is dissociated by expression of dynamitin. This is the first demonstration of the linkage between an hsp90-chaperoned transcription factor and the system for its retrograde movement to the nucleus both in vitro and in vivo.